Comparative proteomic analysis in children with idiopathic short stature (ISS) before and after short‐term recombinant human growth hormone (rhGH) therapy. Issue 7 (4th March 2013) - Heo, Sun Hee; Choi, Jin‐Ho; Kim, Yoo‐Mi; Jung, Chang‐Woo; Lee, Jin; Jin, Hye Young; Kim, Gu‐Hwan; Lee, Beom Hee; Shin, Choong Ho; Yoo, Han‐Wook
<x xml:space="preserve">Abstract</x> This study was undertaken to identify growth hormone (GH) responsive proteins and protein expression patterns by short‐term recombinant human growth hormone (rhGH) therapy in patients with idiopathic short stature (ISS) using proteomic analysis. Seventeen children (14 males and three females) with ISS were included. They were treated with rhGH at a dose of 0.31 ± 0.078 mg/kg/week for 3 months. Immunodepletion of six highly‐abundant serum proteins followed by 2D DIGE analysis, and subsequent MALDI TOF MS, were employed to generate a panel of proteins differentially expressed after short‐term rhGH therapy and verify the differences in serum levels of specific proteins by rhGH therapy. Fourteen spots were differentially expressed after rhGH treatment. Among them, apo E and apo L‐1 expression were consistently enhanced, whereas serum amyloid A was reduced after rhGH therapy. The differential expressions of these proteins were subsequently verified by Western blot analysis using sera of the before and after rhGH treatment. This study suggests that rhGH therapy influences lipoprotein metabolism and enhances apo L‐1 protein expression in ISS patients.